Developing the underdeveloped countries (London ; Macmillan, 1971)
This publication uses diagrammatic maps and vivid prose to demarcate Profiles of the Third World and present an instant challenge to the social conscience. Topics include: the economic impact of colonialism; natural resources and tropical development; growth; expansion of exports and growth of population; theory of development and idea of balanced growth; unbalanced growth; agriculture and the development of West Africa among others.
Includes bibliographical references.
lje 03/10/2018
Loans
Keywords: Economic development; Developing countries